2012
DOI: 10.1007/s00330-012-2479-1
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, image quality and radiation dose comparison of high-pitch spiral and sequential acquisition on 128-slice dual-source CT angiography in children with congenital heart disease

Abstract: • Modern CT provides excellent anatomical detail of congenital heart disease. • Dual source CT systems offer high-pitch spiral and sequential modes. • The high-pitch mode provides high accuracy for the assessment of CHD. • A few images using the high-pitch mode were occasionally slightly degraded. • But the high-pitch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…We achieved a reasonably low effective radiation dose of 0.36 mSv and the mean CTDI vol of 0.31 mGy using a high-pitch 70-kVp mode. These values are distinctively lower than those in some studies and similar to those in other studies [20,23,24,46,47]. We found no other study that compared [43].…”
Section: Discussionsupporting
confidence: 85%
“…We achieved a reasonably low effective radiation dose of 0.36 mSv and the mean CTDI vol of 0.31 mGy using a high-pitch 70-kVp mode. These values are distinctively lower than those in some studies and similar to those in other studies [20,23,24,46,47]. We found no other study that compared [43].…”
Section: Discussionsupporting
confidence: 85%
“…Han and colleagues analyzed a cohort of 70 pediatric patients and found an average ED of 1.7 mSv for retrospectively ECG-gated CTA and 0.9 mSv for prospectively ECG-triggered CTA [8]; this is similar to our findings (in particular when considering the lower pediatric E/DLP conversion factors used in their study). In a population of 40 children aged\2 years, Nie and colleagues calculated a mean ED of 0.29 mSv for prospectively ECGtriggered CTA [19], which is very similar to the 0.37 mSv that we observed for prospectively ECG-triggered CTA in patients\1 year.…”
Section: Discussionsupporting
confidence: 81%
“…Initial studies have suggested that high-pitch acquisition is feasible in pediatric patients and may further reduce radiation dose [7,8,19]. The reported effective doses for highpitch pediatric chest CTA range from 0.17 mSv in a predominantly infant population [19] to 0.9 mSv in a mixed pediatric population [7].…”
Section: Discussionmentioning
confidence: 99%
“…The present study responded to the growing concern over the radiation doses administered to children and applied a novel scanning method. According to the two gating techniques used, children were equally classified into groups A and B (20). In group A, retrospective ECG-gating with an ECG-pulsing technique was applied and the exposure window of this group was adjusted to 35-75% of the cardiac cycle; whereas the exposure window of group B was adjusted to 40-70%.…”
Section: Discussionmentioning
confidence: 99%
“…To optimise the scanning phase, previous studies (20,26) have suggested that the exposure window should be adjusted to 40% of systole as the majority of children with CHD exhibit rapid heart rates. As such, cardiac function cannot be evaluated without a cardiac systole during scanning (27).…”
Section: Grade ------------------------------------------------------mentioning
confidence: 99%